2021
DOI: 10.1016/j.heliyon.2021.e07173
|View full text |Cite
|
Sign up to set email alerts
|

Mental health of young people amidst COVID-19 pandemic in Bangladesh

Abstract: Background: The psychological burden of the coronavirus disease 2019 (COVID-19) outbreak and lockdown strategy among young people not diagnosed with COVID-19 in the general population remains unknown and often have been overlooked. The objective of the study was to assess the prevalence and predictors of anxiety, depression and stress among young people diagnosed with COVID-19 of Bangladesh amidst the pandemic. Methods: A cross-sectional online survey was conducted from 1 May to 30 May 2020 using an online Goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…This study intends to assess the prevalence of depression and stress among university students in Bangladesh during the COVID-19 pandemic regarding their future careers and to identify the factors related to this depression and stress. We found that gender, managing study cost by own, living with family during the pandemic, delaying graduation, less skilled, no internship opportunity, pressure by the family for financial support and start-up plan are notably associated with depression and stress among the students considering their future career; some of which shows consistency with previous studies on university students in other developing countries [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This study intends to assess the prevalence of depression and stress among university students in Bangladesh during the COVID-19 pandemic regarding their future careers and to identify the factors related to this depression and stress. We found that gender, managing study cost by own, living with family during the pandemic, delaying graduation, less skilled, no internship opportunity, pressure by the family for financial support and start-up plan are notably associated with depression and stress among the students considering their future career; some of which shows consistency with previous studies on university students in other developing countries [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 87%
“…During COVID-19, several studies are conducted in Bangladesh based on the depression and anxiety of the students. For example, after the lockdown, a study on Bangladeshi students showed that more than 80% students have mild to severe depression where male students have higher depressive symptoms [ 28 , 29 ]. Also, it was observed that among the underlying factors playing behind this mental breakdown among the young adults, unemployment, financial instability and uncertainty of job were determined as some major culprits [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, there are both similarities and differences between this research and the extant studies on built environment design and mental health that may advance existing understanding and knowledge. Specific to the context of COVID-19, age is negatively correlated with depression and anxiety, which is consistent with Khan et al (2021) . The impact on the daily routine of young people and adults during the COVID-19 lockdown may be more drastic because young people and adults are forced to stay at home when they should be studying and working, which may be one of the reasons for their depression and anxiety.…”
Section: Discussionsupporting
confidence: 76%
“…Data were collected from Sept 08, 2020, to Nov 08, 2020. At that time, it was not feasible to conduct community-based surveys due to the countrywide lockdown implemented by the government (27,28). This self-reported retrospective study was conducted using a standardized questionnaire.…”
Section: Study Design and Timementioning
confidence: 99%